Pleural empyema as a complication of COVID 19 pneumonia in a patient with destroyed lung syndrome (General Practice, 2023)
Introduction. Destroyed lung syndrome is a severedestruction of the pleural parenchyma due to lung infection,mostly caused by tuberculosis. Besides tuberculosis, necrotizingpneumonia may also lead to this disease complication.Pleural empyema is a frequent consequence of the destroyedlung syndrome. Pleural empyema may occur during the COVID-19 infection and is negatively correlated with a favorabledisease outcome.Case report. A male 50 y/o showed up during the oncallshift during the winter COVID-19 wave with a medicalreport from the Internal medicine clinic. His personal historyis significant for his pneumonectomy in 2016. In the past twomonths, he had been treated for pneumonia and COVID-19infection with antibiotics and corticosteroid therapy. Due toprolonged malaise and tachycardia his GP referred him to yetanother chest X-ray and lab work. The chest X-ray showedpleural effusion, so he was promptly referred to an on-callhospital. The on-call physician, after looking into the hospitalreports, consulted an internal medicine doctor and it wasdecided to refer the patient to a thoracic surgeon. He washospitalized for pleural empyema and treated with thoracicdrainage using the system of active aspiration. A year later, hefeels well, and he regained his appetite, and body mass, withoccasional leaking from the thoracic fistule.Conclusion. This case report shows a recurrence ofpleural empyema in a patient with pneumonectomy due tonecrotizing pneumonia and destroyed lung syndrome, complicatedby COVID-19 infection. We aimed to draw the atentionof GPs to diseases and disease complications that arerarely met in GP practice and are not otherwise treated on theprimary healthcare level.
Keywords: destroyed lung syndrome; pleural empyema; COVID-19